2018
DOI: 10.7759/cureus.2169
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Bradycardia with the Long-term Use of Phenytoin and Oxycodone: First Case Report

Abstract: Phenytoin is a medication that is used primarily in the treatment of epilepsy as well as generalized tonic-clonic seizures and status epilepticus. Phenytoin is also considered a class IB antiarrhythmic medication by shortening the duration of the action potential and increasing myocardial conduction. The neurologic adverse effects of phenytoin are well-documented and include altered mental status, ataxia, and nystagmus. Some adverse cardiac manifestations have also been reported, including arrhythmias, hypoten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Although opioids have been used in the treatment of CNCP for decades, only a few studies have looked specifically at the relationship between opioid use and cardiovascular effects [12]. Several studies [13][14][15] have found an increased cardiovascular risk, up to 77%, in patients who receive opioids for the treatment of CNCP (Table 1) [12][13][14][15][16].…”
Section: Cardiovascular Opioid Effectsmentioning
confidence: 99%
“…Although opioids have been used in the treatment of CNCP for decades, only a few studies have looked specifically at the relationship between opioid use and cardiovascular effects [12]. Several studies [13][14][15] have found an increased cardiovascular risk, up to 77%, in patients who receive opioids for the treatment of CNCP (Table 1) [12][13][14][15][16].…”
Section: Cardiovascular Opioid Effectsmentioning
confidence: 99%